Carabelli's trait: Frequency and expression in primary and permanent dentition - Prasun Mukhopadhyay; Santanu Mukhopadhyay (Wolters Kluwer Medknow Publications, 2020)
Aim: Carabelli's trait (CT) is a cusp or groove seen on the palatal surface of the mesiopalatal cusp of primary maxillary second molars and permanent maxillary first molars. The purpose of this study was to determine the frequency and degree of expression of CT in the primary maxillary second molars and permanent first molars in Bengali population. Methods: In this descriptive study, 377 children (193 males and 184 females) of both sexes were examined clinically for the presence of CT. Intraoral examinations were carried out to determine the incidence and degree of expression of a CT for the primary maxillary second molars and permanent first molars. When present, CT was recorded as cusp or pit. Results: The frequency of CT was 45.6% with no significant sex difference (P > 0.05). The prevalence of the trait was more in primary maxillary second molars (38.7%) than in permanent first molars (23.1%). Bilateralism of CT was observed in 79.1% of the cases. Negative expression or pit form of the trait was more common than cuspal configuration. There was a positive association (P = 0.00) between the occurrence of CT in the primary second molars and permanent first molars. Conclusion: The prevalence of CT was more in primary maxillary second molars than in permanent maxillary first molars. The presence of CT in the primary maxillary second molars was positively associated with CT in the maxillary permanent first molars.